Joint compensation of phase and amplitude noise using extended Kalman filter in coherent QAM systems - Pakala, Lalitha; Schmauß, Bernhard (40th European Conference on Optical Communication (ECOC), 2014)
We propose and numerically investigate an optimal carrier phase and amplitude noise estimation (CPANE) algorithm using extended Kalman filter (EKF) for effective mitigation of linear and nonlinear phase noise with simultaneous suppression of amplified spontaneous emission (ASE) noise.
lhft_intern.bib::Pakala2014a